INFLUENCE OF CONGRESS IN SUPPORTING ON ENVIRONMENTAL ISSUE IN RONALD REAGAN ADMINISTRATION - Fatkurrohman Fatkurrohman (Jurnal Kawistara, 2018)
This research aims to analyze the influence of the United States Congress in influencing the policies of the Ronald Reagan administration in ratifying the Montreal Protocol. This research uses one of the models proposed by Graham T. Allison, a bureaucratic political model. This model is used to analyze the political process associated with the bargaining position and compromise between the actors involved in the governments of Ronald Reagan, Congress and DuPont (the company). To understand how these actors play their role in the domestic political process, researchers use qualitative research by collecting data in the form of books, journals and other documents. Explorative methods are used to explore related argumentative basics related to the political process that occurs between the three actors. The result of this study shows that Congress in the era of the Ronald Reagan administration, especially in the House of Representatives is more dominated than the Democratic Party than the Republicans, while in the Senate during 1981-1989, the Democratic Party was only dominant in 1987-1989. The important three things in this research that all actors obtained their interests. Firstly, it is DuPont Company. It received benefits from CFC (Chlorofluorocarbon) changing such as HFC (Hydrofluorocarbon), HC (Hydrocarbon), and PFC (Perfluorocarbon). Secondly, it is Congress Agency. It which was dominated by the members of Democratic Party that stressing on environmental issues could reach their political program such as environmental protection. Thirdly, it is the Executive Agency. It gained benefits in saving of budget $503 million up to $2,8 billion for treating many diseases such as cortical cataract cancer, decrease of body immunity, and environmental problems.